Creatinine accelerates APAP-induced liver damage by increasing oxidative stress through ROS/JNK signaling pathway - Liu, Fang; Liu, Yan; Peng, Qifeng; Wang, Guodong; Tan, Qing; Ou, Zhongyue; Xu, Qishan; Liu, Chixiang; Zuo, Daming; Zhao, Jianbo (Frontiers in Pharmacology, 2022)
Serum creatinine is an endogenous biomarker to estimate glomerular filtration rate (GFR) and is commonly used to assess renal function in clinical practice. Acetaminophen (APAP), the most available analgesic and antipyretic medication, is recommended as the drug of choice for pain control in patients with renal diseases. However, an overdose of APAP can lead to severe acute liver injury, which is also the most common cause of acute liver failure in western countries. The role of creatinine in APAP-induced liver injury is unclear and should be further explored. Herein, clinical data on patients with drug-induced liver injury revealed that the creatinine concentration between 82-442 μmol/L for female and 98–442 μmol/L for male is positively correlated with alanine aminotransferase (ALT), aspartate aminotransferase (AST). While there was no correlation between creatinine and ALT and AST when creatinine concentration is over 442 μmol/L. In addition, mice were administrated with creatinine intraperitoneally for 1 week before APAP injection to investigated the pathophysiological role of creatinine in APAP-induced acute liver injury. The results showed that creatinine administration aggravated hepatic necrosis and elevated serum lactate dehydrogenase (LDH) and ALT levels in mice upon APAP injection. The mechanism study demonstrated that creatinine could increase the production of reactive oxygen activation (ROS) and the activation of c-Jun N-terminal kinase (JNK). Furthermore, the liver injury was alleviated and the difference between APAP-treated mice and APAP combined with creatinine-treated mice was blunted after using specific ROS and JNK inhibitors. Significantly, creatinine stimulation aggravates APAP-induced cell death in HepaRG cells with the same mechanism. In summary, this study proposed that creatinine is closely related with liver function of drug-induced liver injury and exacerbates APAP-induced hepatocyte death by promoting ROS production and JNK activation, thus providing new insight into the usage of APAP in patients with kidney problems.